The viability of using gold mine tailings as a substitute for fine aggregate in concrete mixes - Gani, Saajidah Abdool Rehman (Department of Civil Engineering, 2025)
Urbanization has caused an increase in demand for building materials, some of which requires mined natural resources. These materials produce large volumes of mining wastes (also known as tailings) which have environmental and economic implications. This research investigates the potential of recycling gold mine tailings from the Witwatersrand region as a substitute for fine aggregates in concrete. Laboratory experiments were used to determine the physical properties, such as density and particle size distribution (PSD) and compare these physical properties with the other conventional fine aggregates used in this research, as well as the impact on the fresh and hardened properties of concrete mixes made using Gold mine tailings, focusing on the compressive strength. Gold mine tailings were found to have comparable PSD and fineness modulus to Philippi dune sand, although they contained a higher proportion of fine particles. Concrete mixes using varying replacement ratios of Philippi dune sand with Gold mine tailings were tested. Results indicated that at 28 days, all mixes achieved at least 76% of the reference mix strength. However, higher replacement ratios consistently reduced compressive strength due to increased water demand and resulted in a reduced cohesiveness at the cement-paste interface. Oxygen Permeability Index tests showed excellent results, suggesting low permeability. While the research confirms that replacing fine aggregates with Gold mine tailings results in decreased compressive strength and workability, literature suggests that a partial replacement of fine aggregate with other mine tailings may be possible. Further studies are recommended to determine the chemical composition of other mine tailings, the environmental impacts of using mine tailings in this manner, legislative frameworks, and economic viability to optimize the use of mine tailings in construction.